EVALUASI RIPPARDA DESTINASI SUPER PRIORITAS: PERSPEKTIF KEBERLANJUTAN DAN DAYA SAING - Rahafuna, Muhammad Zumar (Pringgitan, 2023)
Certainty and legal products are important things in the process of developing a country and all elements in it, including tourism through the Tourism Law and its derivative tourism policies. The President of the Republic of Indonesia in a cabinet meeting on July 15 2019 established five super priority destinations (DSP), namely Lake Toba, Borobudur, Mandalika, Likupang and Labuan Bajo with a focus on developing destination quality which is expected to increase tourists' length of stay. Tourism Law No. 10 of 2009 mandates sustainability and competitiveness to be one of the aspects that need to be considered in Indonesia's tourism development. Based on RIPPARDA Super Priority Destination policy and comparative studies, no specific emphasis was found on aspects of sustainability and competitiveness to support the government's plans for the development of five super priority destinations, so that in the planning and making of RIPPARDA for the next period, sustainability and competitiveness aspects must be written specifically to support development aspects.Keywords: Evaluation, Tourism Policy, RIPPARDA, Sustainability, Competitiveness